2022
DOI: 10.1111/jnc.15653
|View full text |Cite
|
Sign up to set email alerts
|

3Dimaging of supraspinal inputs to the thoracic and lumbar spinal cord mapped by retrograde tracing and light‐sheet microscopy

Abstract: The supraspinal inputs play a major role in tuning the hindlimb locomotion function. While most research on spinal cord injury (SCI) with rodents is based on thoracic segments, the difference in connectivity of the supraspinal centers to the thoracic and lumbar cord is still unknown. Here, we combined retrograde tracing and 3D imaging to map the connectivity of supraspinal neurons projecting to thoracic (T9‐vertebral) and lumbar (T13‐vertebral) spinal levels in adult female mice. We dissected the difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Why, then, have changes occurred in such a large network? First, the cells of the rodent motor cortex have fibers that extend to the lumbar spinal cord, but there are also branches in the brainstem and cervical spinal cord ( Lu et al, 2022 ), suggesting that the axonal transection affected the larger network. Second, although we could not subdivide the motor cortex because there were only 244 nodes in the entire brain, analysis by the motor cortex subtype might have revealed that the upper limb region is relatively preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Why, then, have changes occurred in such a large network? First, the cells of the rodent motor cortex have fibers that extend to the lumbar spinal cord, but there are also branches in the brainstem and cervical spinal cord ( Lu et al, 2022 ), suggesting that the axonal transection affected the larger network. Second, although we could not subdivide the motor cortex because there were only 244 nodes in the entire brain, analysis by the motor cortex subtype might have revealed that the upper limb region is relatively preserved.…”
Section: Discussionmentioning
confidence: 99%
“…The laminal plates of C4/5 vertebrae were removed. Then, AAV2-Retro-EGFP (500 nL/site) was injected into the right spinal cord at 0.5 mm lateral to the midline and a depth of 0.7 mm [ 32 , 33 ]. AAV2-Retro -mCherry (500 nL/site) was injected into the left cord using the same method.…”
Section: Methodsmentioning
confidence: 99%
“…Several efforts have been made to improve the resolution or shortcomings of CLSM by using advanced imaging techniques or tools to assess the spatiotemporal expression of proteins. The tools include the multiphoton microscopy two/three-photon imaging (2PEF/2PEF), second-harmonic imaging microscopy (SHIM), light sheet fluorescence microscopy (LSFM), in vivo imaging system (IVIS), chemical tracers, and genetically modified viral tracers such as chemogenetics, optogenetics, and dual virus transduction. …”
Section: Introductionmentioning
confidence: 99%